OPTIMIZATION OF THE PERSONALIZED TREATMENT OF CHILDREN'S RECURRENT BRONCHITIS ON THE BACKGROUND OF COMORBID DISEASES - Achilova Donokhan Nutfullaevna; Ochilova Dilrabo Komil qizi (Bright Mind Publishing, 2025)
This article analyzes the course of recurrent bronchitis in children against the background of comorbid diseases and its personalized (personalized) treatment methods. Based on the results of scientific research, optimal therapeutic approaches are discussed.
Keywords: Children, recurrent bronchitis, comorbid diseases, personalized therapy, pathogenesis, immunomodulators.